2022
DOI: 10.14309/ajg.0000000000002055
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Adenoma Miss Rate With 9-Minute vs 6-Minute Withdrawal Times for Screening Colonoscopy: A Multicenter Randomized Tandem Trial

Abstract: INTRODUCTION: Although the 9-minute mean withdrawal time (m-WT) is often reported to be associated with the optimal adenoma detection rate (ADR), no randomized trials of screening colonoscopy have confirmed the impact of a 9-minute m-WT on adenoma miss rate (AMR) and ADR. METHODS:A multicenter tandem trial was conducted in 11 centers. Seven hundred thirty-three asymptomatic participants were randomized to receive segmental tandem screening colonoscopy with a 9-minute withdrawal, followed by a 6-minute withdra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…The lower overall SDR in the 2 studies by Zhao et al is likely due to the lower rates of SDR in the Chinese population as well as only select centers with capable histopathologists reporting serrated lesions. 13,14 Desai et al; however, did not find an increased SDR with longer WT. 12 Their endoscopists had a high baseline SDR which might have been the factor making the extra WT unnecessary.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…The lower overall SDR in the 2 studies by Zhao et al is likely due to the lower rates of SDR in the Chinese population as well as only select centers with capable histopathologists reporting serrated lesions. 13,14 Desai et al; however, did not find an increased SDR with longer WT. 12 Their endoscopists had a high baseline SDR which might have been the factor making the extra WT unnecessary.…”
Section: Discussionmentioning
confidence: 86%
“…Two of these studies directly compared 6WT with 9-minute withdrawal time (9WT). 13,14 The third study demonstrated a range of WT and data were pooled for 8 to 10 minutes to assume a mean of 9WT. 12 The total number of included patients was 2159 of which 1136 patients were included in the 9-minute withdrawal group (9WT) and 1023 patients in the 6-minute withdrawal group (6WT) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, there are data invalidating the common protocol of performing screening colonoscopy every 30 min with a withdrawal time of 6 min [2,3]. We have data [2] indicating that a 9-min withdrawal time vs. the standard 6-min withdrawal time (excluding polypectomy time) significantly reduces the adenoma miss rate (AMR; 14.6% vs. 36.6%) and the advanced adenoma miss rate (AAMR; 5.3% vs. 46.9%). Moreover, other data provide guidance for a more specific use of withdrawal time [3].…”
mentioning
confidence: 85%